„Zrób to sam/Do it yourself”. Nowe oblicza rzemiosła i rękodzieła w kulturze współczesnej - Orszulak-Dudkowska, Katarzyna (Zeszyty Wiejskie, 2016)
The article presents the “do it yourself” (DIY) phenomenon which is popular in culture nowadays. It constitutes a distinctly noticeable sign of the return to craftwork based on manual work. The author treats this phenomenon as a modern continuation of old handicraft and craft traditions, while at the same time she notices its new functions and socio-cultural meanings. The author recalls historical contexts of the “do it yourself” philosophy in the culture of the West, as well as in native cultural traditions; she also presents current examples of activities of this kind, taken from websites and internet blogs. In the author’s view, the DIY phenomenon is situated in the circle of current trends of design, it is an expression of the criticism of consumerist society and is an ecological attitude towards the natural environment. It also remains strongly connected with the outlook of the involved people and social groups, as well as constituting evidence of people’s creative involvement in their relations with the material world.